O ser justo de Paul Ricoeur e a excelência na formação humana - Ribeiro, Andrey Borges Pimentel (2021)
This thesis is part of the Research Line Fundaments of Educational Processes of the Graduate Course Program in Education of Federal University of Goiás, proposing to investigate the Righteous Human Being of Paul Ricoeur and the excellent human formation, assumed in the sense of true education, paideía. Therefore, the first chapter seeks to understand its hermeneutic phenomenology in the wake of the heideggerian project that puts the being under discussion, problematizing the identity, characterized as sameness (identity, idem) and ipseity (identity, ipse), in a perspective that seeks to reveal the who of the action. This motivates an ethical study, object of the second chapter of this thesis. Then, in the second chapter, an attempt is made to define Paul Ricoeur's Righteous Human Being based on his “little ethics” developed at the end of The Self as Other, 1990. Righteous Human Being is conceived as being good, legal and equitable, but it still persists in the philosopher's concept of the fragile and capable man. At the same time, Righteous Human Being maintains the author's philosophical coherence from the notion of fallible man. Thus, the Righteous Human Being is a fragile and capable man, an open concept of human beings. The third chapter of the thesis makes this reflection on the Righteous Human Being announced by Paul Ricoeur in Kant and in the aristotelian tradition, in an attempt to contribute to the question of excellent human formation, paideía. Kant's moral theory is interpreted in terms of its telos, the principle of humanity that puts man as an end in himself. In carrying out this teleological interpretation of kantian morality, the Righteous Human Being is best understood in the Aristotelian tradition. Thus, Righteous Human Being is investigated in Aristotle, Cicero and Thomas Aquinas, in view of the philosophical anthropology that discusses the human being in the light of the socratic adage and its fundamental question about what justice is. Paideía or humanĭtas is true education, excellent human formation, ethics in its demand for justice that elevates the human to the condition of Righteous Human Being, not as a ready-made, definitive concept, but the human in its unfinished business, in its becoming, disproportionate, an autonomous and vulnerable subject in the fragile and capable man of Paul Ricoeur's hermeneutic phenomenology. Ricoeur's philosophy and its hermeneutic phenomenology maintain the platonic discussion about the justice and truth of the human; their knowledge confirms the importance of education for ethics, politics, the realization of democracy.